2017
DOI: 10.1007/s10266-016-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mandibular movement during chewing of different hardness foods

Abstract: In order to clarify the change in mandibular movement during chewing of foods with different hardness, 20 healthy subjects were asked to chew 3 types of gummy jellies (containing 6, 8, and 10% gelatin), and the masseter muscular activity and the mandibular movement were recorded. The indicators representing the muscular activity (integral value of masseter muscular activity), the mandibular movement (opening distance, masticatory width, cycle time, opening maximum velocity and closing maximum velocity), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…For this reason, the data obtained with the application of the JFLS protocol were particularly useful to demonstrate which conditions of mandibular limitation were more prominent in these patients recently affected by the disorder, which agrees with the findings of the clinical evaluation (OMES). Indeed, in order to bite and grind larger and more consistent foods, respectively, greater vertical movement, bite force and lateral excursion of the jaw are required . As described by Le Révérend et al, modifying food textures, even within the same "food family," would influence masticatory behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the data obtained with the application of the JFLS protocol were particularly useful to demonstrate which conditions of mandibular limitation were more prominent in these patients recently affected by the disorder, which agrees with the findings of the clinical evaluation (OMES). Indeed, in order to bite and grind larger and more consistent foods, respectively, greater vertical movement, bite force and lateral excursion of the jaw are required . As described by Le Révérend et al, modifying food textures, even within the same "food family," would influence masticatory behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Although the symptoms may vary, they affect to a greater or lesser degree the choice, the intake and the pleasure of the food, so that the majority of TMD patients end up modifying their diet in function of this problem . As food texture can affect several aspects of the masticatory process, the evaluation of the perception of patients with TMD symptoms associated or not with occlusal alterations may help understanding how the disorder changes their chewing behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They found that jaw closing velocity was faster for soft jelly than for hard jelly, and found that lateral jaw excursion was enhanced when chewing hard gels. In the study on effects of compositional differences in cheese and cara- Komino and Shiga (2017) was much softer than winegums, and therefore, if the highest gelatin content 10% was increased more, then one might expect to observe the slowing down of the closing velocity. However, their main interest is limited to food samples which are normally eaten in Japan.…”
Section: Effects Of Mechanical Properties Of Foods On Biting Speedmentioning
confidence: 99%
“…More recently, using soft (hardness 69.8 kPa), medium (109.6 kPa), and hard (150.2 kPa) gummy jellies with the same ingredients except gelatin content (6, 8, and 10% for soft, medium, and hard jelly, respectively) Komino and Shiga () reported the maximum closing velocity of 127.9 mm/s for soft jellies, 143.3 mm/s for medium jellies, and 151.7 mm/s for hard jellies. They found that lateral jaw excursion was enhanced when chewing hard gels where subjects could not manage only by vertical movement, which seems to be widely recognized.…”
Section: Textural Profile Analysis: Classification Of Textural Characmentioning
confidence: 99%
See 1 more Smart Citation